ECONOMIC ANALYSIS OF RASPBERRY SUPPLY AND DEMAND FACTORS - Pantić, Nemanja M; Cvijanović, Drago; Imamović, Nedžad (Economics of Agriculture, 2021)
The subject of this research is the analysis of supply and demand of raspberries on the domestic market in order to performe a balance analysis of products and examine the partial inﬂuence of relevant factors on supply and demand. The production and consumption of raspberries in Serbia in the period from 2010-2019 is very dynamic. Raspberry production in the Republic of Serbia has significant comparative advantages compared to production in most other countries. Serbia is considered one of the largest producers of raspberries, but still, regardless of that, its comparative advantages have not been fully valorized and used. The results of the balance analysis of raspberry production and consumption indicate the existence of a surplus and potential for export. The analysis of ANOVA variances established a high correlation dependence and pointed out the need to improve competitiveness in the production of raspberries and final products in order to meet the domestic market and exports to the world market. The obtained results enabled the formulation of regression equations of both the function of raspberry supply and its demand, which can be used to predict these values in the future.